APPLICATION OF GUIDED INQUIRY LEARNING MODELS TO IMPROVE SELF CONCEPT AND LEARNING ACHIEVEMENT - Anita Aryani; Johanes Sapri (UNIB Press, 2019)
This study aimed to describe the application of the inquiry design in learning natural science can improve the creativity of students in the fourth grade of Public Middle School 05 Lebong, describe the application of synoptic design in learning natural science can improve student achievement in class VIII of Public middle School 19 Lebong describes the effectiveness of synoptic design improve the learning achievement of Math students in grade VII Public middle School 19 Lebong. The research is a classroom action research combined with quasi experiments. The subjects of this research are grade VIII.a Public Middle School 19 Lebong as PTK clas, while class VIII.c as control class and exsperimental classVIII.c. The instruments used are observation and test sheets. The technique of data analysis using the formula of the average percentage value of classical learning and t test, while the observation data is analysed with the average score, highest score, lowest score, score difference and the range of values for each criterion. The results showed that the application of synoptic learning design improves students creativity and learning achievement